Strong Convergence Theorems for a Countable Family of Lipschitzian Mappings - Weerayuth Nilsrakoo; Satit Saejung (Abstract and Applied Analysis)
We modify the iterative method introduced by Kim and Xu (2006) for a countable family of Lipschitzian mappings by the hybrid method of Takahashi et al. (2008). Our results include recent ones concerning asymptotically nonexpansive mappings due to Plubtieng and Ungchittrakool (2007) and Zegeye and Shahzad (2008, 2010) as special cases.